Trichodesmium Around Australia: A View From Space - Lin Qi; Menghua Wang; Chuanmin Hu; Douglas G. Capone; Ajit Subramaniam; Edward J. Carpenter; Yuyuan Xie (Geophysical Research Letters, 2023)
Abstract The cyanobacterium Trichodesmium is responsible for approximately half of the ocean's nitrogen input through nitrogen fixation. Although it was first recorded near Australia in the 18th century, the knowledge of where and when large quantity of Trichodesmium around Australia could be found is still lacking. Here, using multi‐band satellite imagery acquired between 2012 and 2021, we fill this knowledge gap through the use of deep learning, designed to recognize both the spectral shapes of individual pixels and spatial morphology of surface aggregations (scums) of Trichodesmium. Trichodesmium scums were found nearly everywhere around Australia, with a cumulative footprint (i.e., where the 10‐year average density is >0.001‰) exceeding 4.6 million km2. Strong seasonality was found, with peak months between September and November. Furthermore, temperature, iron‐rich dust and black carbon aerosols, with the latter being a result of frequent bushfires, play major roles in determining the spatial distributions and seasonality of Trichodesmium.